2019
DOI: 10.6018/rcsar.382261
|View full text |Cite
|
Sign up to set email alerts
|

Does the IASB know the needs of SMEs? A comparative analysis between the IFRS for SMEs and full IFRS due processes

Abstract: Our research contributes to the limited literature on lobbying in accounting standards for SMEs by analysing all comment letters in the due process for the IFRS for SMEs (from 2004 to 2012) and comparing them to all of the 97 IASB’s projects related to full IFRS during the same period of time. Results confirm that the participation of preparers is significantly lower in the international accounting standardisation process for SMEs. Although this reduced participation is compensated by a higher participation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…The content of the 193 comment letters was subsequently classified by type of stakeholder (academics, auditors, investors, standard-setters, preparers, regulator/securities, and others), following the methodology of other studies (e.g. Anantharaman, 2015;Bautista-Mesa, Muñoz-Tomás and Horno-Bueno, 2019;Giner and Arce, 2012) and the classification of the IFAC (2008). In the particular case of preparers, they were then classified by activity sector in order to identify differences in perceptions by sector.…”
Section: Methodsmentioning
confidence: 99%
“…The content of the 193 comment letters was subsequently classified by type of stakeholder (academics, auditors, investors, standard-setters, preparers, regulator/securities, and others), following the methodology of other studies (e.g. Anantharaman, 2015;Bautista-Mesa, Muñoz-Tomás and Horno-Bueno, 2019;Giner and Arce, 2012) and the classification of the IFAC (2008). In the particular case of preparers, they were then classified by activity sector in order to identify differences in perceptions by sector.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of interest of SMEs in adopting the standard may be a consequence of how the IASB developed the standard. Furthermore, prior research by Gassen (2017), Sellami and Gafsi (2018) and Bautista-Mesa et al . (2019) has shown that SMEs are not at all motivated to adopting an international standard.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The lack of interest of SMEs in adopting the standard may be a consequence of how the IASB developed the standard. Furthermore, prior research by Gassen (2017), Sellami and Gafsi (2018) and Bautista-Mesa et al (2019) has shown that SMEs are not at all motivated to adopting an international standard. Mainly because these types of entities do not have international activities and are not interested in seeking foreign investors, being part of an international group or becoming publicly listed (Aboagye-Otchere and Agbeibor, 2012;Bautista-Mesa et al, 2019;Brouwer and Hoogendoorn, 2017;Gassen, 2017;Sellami and Gafsi, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation